Development and Validation of the International students Adjustment Scale in Turkey - Nazir, Dr. Thseen; Öztürk, Lütfiye Sevde (International Journal of Humanities and Education Development (IJHED), 2022)
Globalization had attracted millions of students around the world and there is a huge flux of students who are travelling abroad for educational purposes. The aim of these students is to gain education and achieve their dreams. But travelling abroad for education and living in a foreign country is not an easy process. During this educational journey and transition from their home country to host country international students face huge challenges of adaptation and the challenges can be in terms of Academics, socio-cultural, personal, etc. So in order to acheieve the main goal of education, International students must adapt to the new envirnoment of the host country. The study aimed to develop validity and reliability of the International adjustment scale in Turkey. A pool of 100 statements was reduced to 35 after validation resulting in five distinct domains of adjustment, such as Academic adjustment (11), Social adjustment (9), Personal adjustment (6), General Living adjustment (4) and Institutional adjustment (3). The multidimensional adjustment was developed and validated for International students in Turkey.